Foaming agent for extinguishing water-soluble combustible liquids - Kondakova, Яна Александровна; Navrotskiy, Олег Дмитриевич; Ivanov, Игорь Юрьевич (Journal of Civil Protection, 2022)
Purpose. Development of a foaming agent for the purpose of extinguishing water-soluble combustible liquids. Methods. Theoretical research methods (analysis, synthesis), as well as empirical ones – measuring the dynamic viscosity of polymer solutions, testing the foam stability on the surface of water-soluble combustible liquids – are used in the work. Findings. Measurements of the viscosity values of polymer solutions were carried out and the maximum value of the polymer concentration was determined, at which the viscosity of the foaming agent is acceptable for use by pumping units of fire trucks; a technique has been developed for determining the stability of foam on the surface of water-soluble combustible liquids. Application field of research. The results obtained are of practical importance and can be used in the development of foam concentrate formulations, and the developed method will make it possible to determine the foam stability on the surface of water-soluble combustible liquids in laboratory conditions.